The Digital Revolution, 3D Printing, and Innovation as Data. Issue 5 (6th July 2017) - Rindfleisch, Aric; O'Hern, Matthew; Sachdev, Vishal
Abstract : The digital revolution has created a data‐rich environment. Increasingly, firms are seeking to acquire and analyze a variety of consumer data such as online shopping, social media, and web browsing behavior to enhance their innovation activities. This approach is termed "Innovation from Data." At the same time, a growing number of consumers are gaining the ability to transform digital data into innovative physical products through the use of new tools such as audio and video editing software and 3D printing technology. This approach is termed "Innovation as Data." These two approaches differ substantially in terms of their views on the role of consumers, the relevance of firms, and the nature of products. This article introduces the concept of Innovation as Data and discusses its relation to the digital revolution in general and 3D printing in particular. In addition, it offers a set of recommendations for managers seeking to leverage this new innovation approach and ideas for scholars interested in researching this intriguing domain.